Spatio Temporal Analysis of Urban Heat Island Using Landsat 8 Oli/Tirs Imagery in Klaten District In 2013 – 2021 - Wahyudi, Hendra; Jumadi, J (Amcolabora, 2024)
Klaten Regency is one of the areas that has experienced changes in use over time, such as agricultural land becoming built-up or non-agricultural land. This has an impact on the increase in air temperature which can lead to the occurrence of the phenomenon of the Heat Island or Urban Heat Island. This study aims to determine the spatio-temporal variation of vegetation index value (NDVI), Surface Temperature and in Klaten Regency in 2013 - 2021 and determine the relationship between vegetation index value (NDVI) and UHI in Klaten Regency. The method used in this research is Landsat 8 image data processing such as NDVI, LST and UHI calculation to get the final result. Meanwhile, to get the relationship between NDVI and Surface Temperature related to the UHI phenomenon, simple regression testing was carried out. The results obtained from the processing results show that Klaten Regency is dominated by vegetation cover density with very high and high classifications despite the decrease in area from 2013 to 2021. Surface temperature in Klaten Regency is dominated by surface temperatures within the range of 25 - 28o C spread across the entire region from 2013 to 2021. The results of the linear regression have a coefficient value of r2 where the value shows results with a value of 0.377. The result of the coefficient of determination shows that the amount of influence obtained from the density of vegetation land cover with an average surface temperature of 37.7% where the rest can be influenced by other factors.